Concurrent training and interindividual response in women with a high number of metabolic syndrome risk factors - Delgado-Floody, Pedro; Chirosa-Ríos, Luis; Caamaño-Navarrete, Felipe; Valdés-Badilla, Pablo; Herrera-Valenzuela, Tomás; Monsalves-Álvarez, Matías; Núñez-Espinosa, Cristian; Castro-Sepulveda, Mauricio; Guzmán-Muñoz, Eduardo; Andrade, David C.; Álvarez, Cristian (Frontiers in Physiology, 2022)
This study examined the effects and NRs prevalence after 20-weeks of concurrent training in severely obese women with a high load of MetS risk factors (≥3). Twenty-eight women with morbid obesity participated in an exercise training intervention and were allocated to two groups based on their high (i.e., ≥3 MetS, n=11) or low load (i.e., <3 MetS markers n=17) of MetS risk factors. The main outcomes were waist circumference (WC), fasting plasma glucose (FPG), high-density lipids (HDL-c), triglycerides (Tg), systolic (SBP) and diastolic (DBP) blood pressure, and secondary outcomes were body composition, anthropometric and physical fitness, determined before and after 20-weeks of intervention. A significant different (all p<0.05) prevalence of NRs between H-MetS vs. L-MetS group (respectively) in WC (NRs 18.2% vs. 41.1%), SBP (NRs 72.7% vs. 47.0%), DBP (NRs 54.5% vs. 76.4%), FPG (NRs 100% vs. 64.8%), and HDL-c (NRs 90.9% vs. 64.7%) were observed. In addition, H-MetS group evidenced marked changes (all p<0.05) on systolic BP (SBP –10.2 mmHg), fasting plasma glucose (–5.8 mg/dL), HDL-c (+4.0 mg/dL), and Tg (–8.8 mg/dL). Contrarily, L-MetS group only showed significant changes in WC (–3.8 cm, p=0.009). Comparing H-MetS vs. L-MetS group, significant differences were observed in ∆FPG (–5.8 vs. +0.3 mg/dL, p=0.027). The NRs prevalence was heterogeneously distributed between H- to L-MetS on primary and secondary outcomes after 20-weeks of concurrent training. Therefore, a high to the low risk to suffer metabolic syndrome is not pivotal to determining NRs after a concurrent training period.